The impact of the 1989 change in bank capital standards on loan loss provisions and loan write-offs - Kim, Myung-Sun; Kross, William (Journal of Accounting and Economics, 1998)
We investigate whether banks with low capital ratios use accounting accruals for capital ratio management. We focus on a time where we expect a change in bank managers behavior regarding certain accruals. In 1989 regulatory changes created (removed) incentives to depress loan loss provisions (write-offs) after (before) 1989. Our results show that banks with low capital ratios reduced their loan loss provisions and increased write-offs during the 1990–1992 period compared to the 1985–1988 period. Banks with high capital ratios exhibited no difference in loss provisions, but did significantly increase loan write-offs during 1990–92.